Analisa Unjuk Kerja Blower Sentrifugal Pada Mesin Turbo Chopper Jerami Padi Sebagai Pakan Ternak Alternatif - Darianto, Darianto; Kurniawan, Fadly Ahmad; Zulfikar, Zulfikar; Iswandi, Iswandi; Hutasoit, Nicolas Sabar (CV. IRA PUBLISHING, 2023)
This study aims to analyze the performance of a centrifugal blower in a Turbo Chopper for Rice Straw as Ruminant Livestock Feed. Conducted over six months at a machine production workshop in Medan Perjuangan, the research employed a qualitative method. The focus was on the blower's impeller, a critical component for increasing air pressure. Tests were performed on impellers with varying numbers of blades (4, 6, and 8) at a constant speed of 1400 rpm. The results showed that the impeller with 4 blades produced the highest wind speed of 4.8 m/s and the greatest efficiency of 0.029%. The study also included an analysis of the blower's torque, flow capacity, and efficiency. These findings are significant for industrial applications, particularly in the process of chopping rice straw, where the centrifugal blower can enhance operational efficiency and effectiveness. This study provides insights into the use of centrifugal blowers to improve the performance of agricultural equipment and potential applications in other industries.